PERUBAHAN POLA PEWARISAN NILAI BUDAYA LOKAL DALAM PEMBENTUKAN KARAKTER ANAK DI KELURAHAN TOSURAYA BARAT KECAMATAN RATAHAN KABUPATEN MINAHASA TENGGARA - Yulianty Frilly Tampinongkol; Djefry Deeng; Mahyudin Damis (Universitas Sam Ratulangi, 2021)
Parenting, in addition to all forms and processes of interaction that occur between parents and children, is also a certain parenting pattern in the family that will affect the development of the child's personality. The personality of children after stepping on adolescence certainly cannot be separated how their parents instill cultural values that live in the society in which they live. Every parent wants the best for their children. This desire will then form a parenting that will be instilled and passed on by the parents to their children.The current generation seems to be increasingly losing the ability and creativity in understanding the principles of local cultural values and traditions, one example, according to parents (Pasan tribal people) a child who passes in front of parents, must ya'sumambing (ducking road while lowering hands). However, now this habit has gradually disappeared and changed ordinary attitudes and arrogant attitudes to mess with his parents, even the attitude of ya'sumambing replaced with hello or ces and so on. There is also a system of cultural values inherited by previous parents such as behaving 'sihadat alud' (manners), 'muha-hormat' (mutual respect), 'tarangtarang: tuar' (firm and consistent), 'matulir karekenan' (honesty) and others. The above values are inherited parents when gathering to eat together (dinner), even they tell when the child makes a mistake. However, over time the current generation seems to be losing understanding of the principles of local cultural values and their traditions.Â Keywords: parenting, change, cultural values